Laminar Natural Convection in nonrectangular Enclosure with and without Fins (Journal of Engineering, 2012)
In the present work, steady, laminar natural convection in nonrectangular enclosures is analyzed numerically with and without fin. Vertical walls insulated while horizontal walls maintained isothermal at different temperature and the fin was placed on horizontal surface. The length of fin was equal (B/L=0.22, 0.44 and 0.66) and thickness of fin was constant. Various parameters are studied: Rayleigh number (from 104 to 107 ), Prandtl number (0.7), number of fin change from (1-3) and aspect ratio (H/L= 0.15 to 0.5). The problem is formulated in terms of the vorticity-stream function procedure. A numerical solution based on program in Fortran 90 with Tec plot program. The finite difference method is used. Streamlines and isotherms are presented for different values of parameters studied. A Nusselt number correlation is derived by using program (DGA v1.00) and mean Nusselt numbers on hot walls are also calculated at different cases. The results show the mean Nusselt numbers decreases with increasing aspect ratio (H/L).Also, predictions reveal a decrease in heat transfer in the presence of fins. The results of the calculations are compared with the previous works and it showed a good agreement.